1995
DOI: 10.3171/jns.1995.82.4.0595
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intrathecally administered narcotic and nonnarcotic analgesics for experimental chronic neuropathic pain

Abstract: The antinociceptive actions of morphine and tizanidine (an alpha 2-adrenergic agonist) administered intrathecally in a rat model of mononeuropathic pain were investigated. Tizanidine increased to normal levels the intensity of a noxious pressure stimulus required to induce paw withdrawal (p < 0.01) and decreased the duration of limb withdrawal from both normal-temperature and cooled floors in a dose-dependent manner (p < 0.01). Tizanidine had virtually no effect on the latency of paw withdrawal from a noxious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…From a clinical point of view, this is promising because, in this study, the effects of melanocortins appear to be specific for the allodynia associated with a neuropathic pain state, without altering normal pain sensation by inducing a more general analgesia. This specificity for the hyperalgesia underlying neuropathic pain without affecting baseline pain detection has also been reported for the ␣2-adrenergic agonist tizanidine (Leiphart et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…From a clinical point of view, this is promising because, in this study, the effects of melanocortins appear to be specific for the allodynia associated with a neuropathic pain state, without altering normal pain sensation by inducing a more general analgesia. This specificity for the hyperalgesia underlying neuropathic pain without affecting baseline pain detection has also been reported for the ␣2-adrenergic agonist tizanidine (Leiphart et al, 1995).…”
Section: Discussionmentioning
confidence: 85%
“…The diminished availability of functionally active spinal opioid receptors following nerve injury could be instrumental to the reduced effectiveness of intrathecally administered opioids [21,22]. Nerve ligation experiments conducted in the rat give rise to the assumption that intraperitoneally and intraventricularly applied morphine leads to a reduction of tactile allodynia much more via supraspinal than via spinal Ì-opioid receptors [23].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-2 adrenoceptor agonists have been reported to be useful adjuncts in the treatment of chronic pain syndromes in animal and human studies [175][176][177]. Lee & Yaksh [178] demonstrated that the intrathecal administration clonidine or MK-801, an N-methyl-D-aspartate antagonist (NMDA), abolished, in a dose-dependent manner, a model of neuropathic pain in rats.…”
Section: Chronic Painmentioning
confidence: 99%